INOVASI PENGELOLAAN KURIKULUM - Emi Wijayani (Manajer Pendididikan, 2016)
The purpose of this research is to describe innovation of curriculum mangement in public yuniour high school 1 Ketahun north Bengkulu. The method of this research was a describtive qualitative study. The data collecting techique used by interview, observation and documentation. The data analysis used by reduction data, presenting data and conclution. Theresult of this researeh showed that: 1) the planning was done by arraging the vision, mision, curriculum, syllabus, lesson plan, a year pregram, semester program and educational schoolcalender, 2) the organization was done by the distribution of teaching asignment, 3) the implementasi was done by choosing method, media of reaching and assessment, 4) the evaluationwas done by supervision of teaching.Keywords: innovation, curriculum, mangement